Estimation of modern glaciers of a Graham Coast (Antarctic peninsula) and islands of the Argentina archipelago - V. F. Gryschenko (Ukrainian Antarctic Journal, 2006)
In operation the results of glaciological researches, executed within the first 10 years of existence of the Ukrainian Antarctic station the Academic Vernadsky are stated: mass-balance supervision on a glacier Home of Galindez island (in a complex with meteorological), revealing of features of a mode and characteristics of a snow cover in area of station, conditions of formation of icebergs in sea water areas and snow avalanches on the Antarctic peninsula; by results of reconnaissance investigations with application of visual inspection, the photo shootings and fototheodolits operations, cartographical material and space pictures are surveyed and are described of continental removal glaciers of the Graham Coast and island ice caps of the Argentina archipelago.